Theory and practice in Essene law - Amihay, Aryeh (Oxford University Press, 2016)
Presenting a novel approach for the study of law in the Dead Sea Scrolls, this book is conveniently divided into concepts and practices, highlighting the discrepancies between the two. It is a valuable study for anyone interested in Jewish law, legal history, sectarianism and communal life